Building Partner Cooperation between Teachers and Parents - Bar Šteh; Jana Kalin (Center for Educational Policy Studies Journal)
This paper presents the goals of teacher-parent cooperation, various potential models for establishing mutual cooperation, and the conditions required to achieve quality interactive cooperation. The partnership model is highlighted as an optimal model of interactive cooperation between teachers and parents, as it includes the distribution of expertise and control with the purpose of ensuring optimal education for children. It enables the creation of an interactive working relationship in which all of those involved are respected and recognised in their efforts to achieve common goals. The second part presents the findings of an empirical study carried out on a representative sample of Slovene primary schools. Teachers (N = 467) and parents (N = 1,690) were asked to express their opinions about the need for mutual cooperation, their view of each other when fulfilling their respective roles, and where they perceive the main obstacles to mutual cooperation. It became evident that teachers and parents have doubts about each other’s competence. This does not form a solid base on which to establish and build the necessary partner relationship, and along with it mutual cooperation. Yet both groups to a large extent agree that teacher-parent cooperation is both necessary and useful. This gives rise to the question as to how to ensure that schools adopt policies promoting opportunities for better understanding, for building quality mutual relations and for parents to become more actively involved.